REPORT ON OPEN MULTICENTRAL RESEARCH PROGRAM “PRIORITY” IN CLINICAL PRACTICE. (PEKTROL – QUALITY OF LIFE IN PATIENTS WITH STABLE ANGINA PECTORIS TREATED WITH ISOSORBIDE-5-MONONITRATE IN LONG-ACTING PRESENTATION) - Yu. A. Karpov (Рациональная фармакотерапия в кардиологии)
Aim. In multicentral program PRIORITY to estimate the efficacy of antianginal therapy after switching patients with stable angina from therapy with short-acting nitrates or isosorbide dinitrate in long-term acting formulation to therapy with isosorbide-5-mononitrate (Pectrol, KRKA, Slovenia) in once daily administrated presentation. Materials and methods. PRIORITY program was held in out-patient clinics of 14 cities. 286 patients with stable angina, who took short-acting nitrates or isosorbide dinitrate in long-term acting formulation, were included in research. Patients were switched without any break to the therapy with isosorbide-5-mononitrate (ISMN) in doze of 40 mg once a day , concomitant therapy was not changed. Initially and after 3 months of treatment with ISMN angina functional class, current therapy with nitrates and concomitant therapy were defined. Quality of life was also determined by questionnaire. Results. 275 patients finished programand 261 of themwere completely corresponded to the study protocol. The treatment with ISMN reduced the frequency and duration of angina attacks (p<0,001), the frequency of sublingual nitroglycerine intake, resulted in the reduction of functional class of angina (p<0, 0001), the increase in walk distance without chest pain or dyspnoea (p<0, 0001). According to questioning 3 months treatment with ISMN resulted in physical exercise tolerance increase (p<0, 0001), reduction in number of side-effects of nitrates therapy (p<0, 0001) and frequency of angina attacks (p<0, 0001). Intensity of psychological discomfort was reduced (p<0,0001) and satisfaction with therapy was increased (p<0, 0001). Conclusion. Switching from short-acting nitrates or isosorbide dinitrate in long-term acting formulation to the therapy with ISMN showed corrective influence on life quality in patients with stable angina: frequency and duration of angina attacks significantly reduced, physical exercise tolerance increased, psycho-emotional condition and patient compliance improved.